2013
DOI: 10.1016/j.jcorpfin.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Does political capital create value in the IPO market? Evidence from China

Abstract: This study examines the value of political capital in the Chinese IPO market. We find a positive relationship between a politically connected executive and the probability of IPO approval of entrepreneurial firms. We further identify that shareholders value those connections and give a market premium to connected firms after the firms go public. We provide evidence that other types of political capital gained through external sources, such as politically connected sponsors and PE investors, also bring benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(76 citation statements)
references
References 40 publications
3
72
1
Order By: Relevance
“…They found that, compared with firms without political connection, politically-connected firms experience less financing constraints [19]. Liu et al (2013) examined the role of political connection in the Chinese IPO market and found a positive relationship between political connection and the possibility of IPO approval [15]. In addition to financial access, Houston et al (2014) explored how political connection affects the cost of bank loans and found that firms with political ties usually have lower bank loan costs [41].…”
Section: The Roles Of Political Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that, compared with firms without political connection, politically-connected firms experience less financing constraints [19]. Liu et al (2013) examined the role of political connection in the Chinese IPO market and found a positive relationship between political connection and the possibility of IPO approval [15]. In addition to financial access, Houston et al (2014) explored how political connection affects the cost of bank loans and found that firms with political ties usually have lower bank loan costs [41].…”
Section: The Roles Of Political Connectionmentioning
confidence: 99%
“…However, these studies mainly focus on board structure or external governance mechanisms. There is a stream of research discussing the role of political connection in listed companies' operation decisions, such as tax payment [13], financing [14,15], and quality management activities [16]. A more recent study argues that political connections are also important parts of governance structures, and plays a key role in China [17].…”
Section: Introductionmentioning
confidence: 99%
“…We then went through each of these articles and dropped nonempirical articles as well as empirical studies that focused on IJVs, overseas Chinese firms (including those in Hong Kong, Macau, and Taiwan), or foreign direct investments in China. We also excluded empirical studies that are purely about the social ties and networks of top managers (e.g., Li, Yao, Sue-Chan, & Xi, 2011;Liu, Tang, & Tian, 2013;Peng & Luo, 2000) or top management team composition and processes (e.g., Chen, Liu, & Tjosvold, 2005;Qian, Cao, & Takeuchi, 2013). We included some of these studies in our review only if they address the principal-agent conflict or the principal-principal conflict caused by separation of ownership and control.…”
Section: Introductionmentioning
confidence: 99%
“…Our choice of instrumental variable is the regional marketization index, which is highly correlated with the CCG Index, but is uncorrelated with firm performance. This index is provided by Fan et al and has been widely used as an instrumental variable in the literature [40][41][42].…”
Section: Corporate Governance and Firm Performancementioning
confidence: 99%